Case Report: A de novo Variant in NALCN Associated With CLIFAHDD Syndrome in a Chinese Infant - Zhenyu Liao; Yali Liu; Yimin Wang; Yimin Wang; Qin Lu; Qin Lu; Yu Peng; Qingsong Liu (Frontiers Media S.A., 2022)
BackgroundThe NALCN encodes a sodium ion leak channel that regulates nerve-resting conductance and excitability. NALCN variants are associated with two neurodevelopmental disorders, one is CLIFAHDD (autosomal dominant congenital contractures of the limbs and face, hypotonia, and developmental delay, OMIM #616266) and another is IHPRF (infantile hypotonia with psychomotor retardation, and characteristic facies 1, OMIM #615419).Case PresentationIn the current study, a Chinese infant that manifested abnormal facial features, adducted thumbs, and neurodevelopmental retardation was diagnosed with CLIFAHDD syndrome. A trio-based whole-exome sequencing revealed that the infant harbored a de novo variant of the NALCN gene (c.4300A>G, p.I1434V).ConclusionsOur findings further enriched the variant spectrum of the NALCN gene and may expand the clinical range of NALCN-related disorders.